Pengaruh Faktor Spesifik Bank dan Faktor Makroekonomi terhadap Pertumbuhan Laba Perbankan di Indonesia - M. A. Emeraldy Rajaya; Isni Andriana; Kemas Muhammad Thamrin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the influence between bank-specific factors and macroeconomic factors on banking profit growth in Indonesia. The population in this study were all banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2022, namely 47 banking sector companies with a research sample of 9 companies. Using a panel data approach, this study places bank-specific factors and macroeconomic factors as independent variables consisting of return on assets (ROA), loans to deposit ratio (LDR), non-performing loans (NPL), inflation, interest rates and exchange rates. Data was collected from the Indonesia Stock Exchange (BEI), Bank Indonesia and BPS. The results showed that ROA has a significant positive effect on profit growth. LDR has no effect on profit growth and NPL has a significant negative effect on profit growth. Inflation has a significant positive effect on profit growth while interest rates and exchange rates have no effect on profit growth.